Being alive with poetry: sustaining the self by writing poetry. Issue 1 (2nd January 2019) - Sharma, Daneshwar
ABSTRACT: The adolescent experience of death of a family member can lead to depression and suicidal tendencies. The article explores this experience of the researcher as a teenager. In the qualitative research framework, the autobiographical poems are used as data. The artistic ways of processing the lived experiences and the subsequent emotions have become a vital part of qualitative research.